Red Rosa : a graphic biography of Rosa Luxemburg - Evans, Kate, 1972-; Buhle, Paul, 1944-; Rosa-Luxemburg-Stiftung. (London : Verso Books, 2015)
"A giant of the political left, Rosa Luxemburg is one of the foremost minds in the canon of revolutionary socialist thought. But she was much more than just a thinker. She made herself heard in a world inimical to the voices of strong-willed women. She overcame physical infirmity and the prejudice she faced as a Jew to become an active revolutionary whose philosophy enriched every corner of an incredibly productive and creative life--her many friendships, her sexual intimacies, and her love of science, nature and art." --
Includes bibliographical references.
Keywords: Luxemburg, Rosa, -- 1871-1919 -- Comic books, strips, etc; Socialists -- Poland -- Biography -- Comic books, strips, etc; Communism -- Germany -- History -- 20th century -- Comic books, strips, etc; Women socialists -- Comic books, strips, etc; Jewish socialists -- Comic books, strips, etc; Germany -- Politics and government -- 1888-1918 -- Comic books, strips, etc; Graphic novels; Biographical comics